Pressure effect on the Fermi surface and electronic structure of LuGa₃ and TmGa₃ - Pluzhnikov, V.B.; Grechnev, G.E.; Czopnik, A.; Eriksson, O. (Физика низких температур, 2005)
The Fermi surfaces and cyclotron masses of LuGa₃ and TmGa₃ compounds are studied by means
of the de Haas—van Alphen effect technique under pressure. The highly anisotropic pressure
dependences of the de Haas—van Alphen frequencies and cyclotron masses have been observed in
both compounds. Concurrently, the ab initio calculations of the volume-dependent band structures
have been carried out for these compounds, including ferromagnetic configuration phase of
TmGa₃, by employing a relativistic version of the full-potential linear muffin-tin orbital method
within the local spin-density approximation. The experimental data have been analysed on the basis
of the calculated volume-dependent band structures and compared with the corresponding pressure
effects in the isostructural compound ErGa₃.